2019
DOI: 10.1002/iub.2099
|View full text |Cite
|
Sign up to set email alerts
|

The modulatory effects of luteolin on cyclic AMP/Ciliary neurotrophic factor signaling pathway in experimentally induced autoimmune encephalomyelitis

Abstract: Multiple sclerosis (MS) is considered to be an autoimmune disorder of the central nervous system (CNS) manifested by chronic inflammation. Although its etiology is not completely understood, inflammation and apoptosis are known to be major players involved in its pathogenesis. Luteolin, the naturally occurring flavonoid, is known by strong antioxidant and anti‐inflammatory properties, yet research studies about its therapeutic role in MS are still lacking. The study aimed to provide insight into effects of lut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…cAMP levels were decreased in the cerebrospinal fluids of MS patients, and inhibition of the cAMP/CREB signaling axis attenuated CNTF expression. Compared to EAE mice, luteolin-treated EAE mice demonstrated improved clinical motor function, reduced inflammatory infiltration of brain tissues, upregulated ciliary neurotrophic factor (CNTF) expression, significantly increased levels of cAMP and total antioxidant capacity (TAC) of the brain and significantly reduced levels of cleaved caspase 3, nuclear factor kappa-B (NF-κB) and macrophage inflammatory protein (MIP)-1α [ 142 ].…”
Section: Natural Compounds Against Oxidative Stress In Animal Models ...mentioning
confidence: 99%
“…cAMP levels were decreased in the cerebrospinal fluids of MS patients, and inhibition of the cAMP/CREB signaling axis attenuated CNTF expression. Compared to EAE mice, luteolin-treated EAE mice demonstrated improved clinical motor function, reduced inflammatory infiltration of brain tissues, upregulated ciliary neurotrophic factor (CNTF) expression, significantly increased levels of cAMP and total antioxidant capacity (TAC) of the brain and significantly reduced levels of cleaved caspase 3, nuclear factor kappa-B (NF-κB) and macrophage inflammatory protein (MIP)-1α [ 142 ].…”
Section: Natural Compounds Against Oxidative Stress In Animal Models ...mentioning
confidence: 99%
“…In another study, the luteolin's effect on neuroinflammation, oxidative stress, synaptic plasticity, and impaired cognitive impairment was tested on adult Sprague Dawley rats and it was determined that luteolin reduced chronic cerebral hypoperfusion-induced microglia overactivation along with other benefits [ 47 ]. Moreover, a study conducted by El-Deeb et al focused on investigating luteolin's effect on autoimmune encephalomyelitis showed that flavone has anti-inflammatory, antiapoptotic, and antineurotrophic activities also in multiple sclerosis [ 48 ].…”
Section: Preclinical Pharmacological Activities Of Luteolin: In Vivo Evidencementioning
confidence: 99%
“…Lut is neuroprotective in various diseases including epilepsy, autism spectrum disorders, Alzheimer’s disease, Parkinson’s disease, traumatic brain injury, and MS ( Nabavi et al, 2015a ). Oral administration and intraperitoneal injection are the main administration routes for Lut for a number of disorder models ( El-Deeb et al, 2019 ; Imran et al, 2019 ). The dosages of Lut range from 1.2 to 50 mg/kg, and in vivo studies have verified that it has a significant effect in alleviating various diseases such as cancer and MS ( El-Deeb et al, 2019 ; Imran et al, 2019 ).…”
Section: Nature Productsmentioning
confidence: 99%
“…Oral administration and intraperitoneal injection are the main administration routes for Lut for a number of disorder models ( El-Deeb et al, 2019 ; Imran et al, 2019 ). The dosages of Lut range from 1.2 to 50 mg/kg, and in vivo studies have verified that it has a significant effect in alleviating various diseases such as cancer and MS ( El-Deeb et al, 2019 ; Imran et al, 2019 ). Lut promotes ciliary neurotrophic factor (CNTF) expression and has the ability to increase cAMP and the total antioxidant capacity.…”
Section: Nature Productsmentioning
confidence: 99%
See 1 more Smart Citation